EVALUASI SISTEM INFORMASI AKUNTANSI DENGAN PENDEKATAN SIKLUS PADA PENJUALAN TUNAI DAN KREDIT PT SO GOOD FOOD DEPO SOLO - Wulandari, Kartikaningsih Risa (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
Sales is an important aspect for the company in order to maximizing profit, sales consist of cash sales and credit sales. Foul in management of sales will inflict a financial loss of company. An effective accounting information system is required. Effectiveness of accounting system requires the approval and support of all levels of management. It’s needed to delegate authority and responsibilities in order to achieve efficiency and of course with an effective accounting system and will strengthen the internal control structure of assets, liabilities, equity, revenues, and expenses of the company which one of the activity is sales. The purpose of this study is to analyze the effectiveness of accounting system information for cash and credit cycle which has been doing in PT SO GOOD FOOD depo Solo. The conclusion is accounting system information with the nearest cycle for cash and credit sales PT SO GOOD FOOD depo Solo has been really effective. Because it has been doing a good internal controlling. Keywords: accounting system information, cash and credit sales